PEMBUATAN TUTORIAL CARA CEPAT MEMBACA DAN BERHITUNG PADA ANAK BERBASIS MULTIMEDIA MENGGUNAKAN MACROMEDIA FLASH 8 - Ade Putra; Asnawati Asnawati; Eko Suryana (UNIVED Press, 2016)
In the future today children today tend to be interested in playing the game from the study, because the development of the game world is now more rapidly and attractive compared to developments in the world of education, this is what makes children more interested in playing games than on learning. in addition, the old learning methods of reading and exercise, most of the children in modern times are now less interested and tend to be lazy to learn such a way. require a way for children to play and indirectly while learning. Computer-based teaching tool is expected to help overcome this problem. in addition, teaching tool like this can also ease the burden on teachers, so that the learning process can run well and the materials being taught can be understood by students. through learning how to use a computer, a lesson can be delivered in an interactive form and can illustrate a concept through animation, sound and attractive demonstration. this application allows students to learn without a time limit. The purpose of the research to make reading tutorial how to quickly and counting in child-based multimedia using macromedia flash 8.0. teaching tool that utilizes computers to deliver the materials to be taught so-called computer assisted instruction (cai). computer assisted instruction is a computer-based teaching aids with an interactive program. by using this device, the learning process becomes more active. this device can be used as a primary tool or a teaching tool. Based on the results of this study concluded that the tutorial how to quickly learn and numeracy can add to the spirit of learning students, this is because students are actively involved and participate in learning using this tutorial, so that learning becomes fun, the students begin to mention the numbers and letters with its own language, though still with the help of a teacher.Key words : Tutorial, Multimedia, Macromedia Flash